Periodontitis as a Novel Contributor of Adipose Tissue Inflammation Promotes Insulin Resistance in a Rat Model. Issue 11 (1st November 2013) - Su, Yuan; Wang, Dan; Xuan, Dongying; Ni, Jia; Luo, Shigao; Xie, Baoyi; Zhang, Jincai
Abstract : Background: Recent studies have indicated that the chronic low‐grade inflammation induced by periodontitis is related to obesity and type 2 diabetes mellitus. The purpose of this study is to investigate the effects of periodontitis on obesity‐related adipose tissue inflammation and subsequent systemic insulin resistance in a rat model. Methods: Thirty‐two rats were divided into four groups of eight: 1) obese rats with periodontitis (combination group); 2) obese rats without periodontitis (obesity group); 3) normal rats with periodontitis (periodontitis group); and 4) normal rats without periodontitis (control group). Monosodium glutamate was used to induce obesity during the early postnatal period. Periodontitis was induced by ligatures for 8 weeks. Morphologic features of white adipose tissue (WAT) and islets were observed, and fasting plasma glucose and insulin concentrations and homeostasis model assessment for insulin (HOMA‐IR) were measured at 5 months. Differences among groups were compared with the Fisher post hoc least significant difference test. Results: A slight increase of stromal vascular fractions (SVFs) and macrophage infiltration in the WAT of the periodontitis group was observed. Significant proliferation of SVFs and macrophage infiltration were induced in the combination group. HOMA‐IR scores in the combination and periodontitis groups were higher than in the obesity and control groups, respectively. The disturbance of islet architecture was consistent with a high HOMA‐IR score in the combination group. Conclusions: Periodontitis induced initial stages of WAT inflammation and acted as a contributing factor to exacerbate proinflammatory phenotype of WAT and promote the development of insulin resistance in the obese rat model.